PENGARUH PENDEKATAN CONTEXSTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS BERDASARKAN MINAT BELAJAR SISWA SD NEGRI 93 PALEMBANG - Eci Lestari; Nila Kesumawati; Endie Riyoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background to this research is that the critical thinking skills of students in class V are still in a fairly low category and the delivery of learning material is still very simple, namely using a conventional teacher-centered learning approach. The method in this research is an experimental sequence and the population in this research is all class V at SD Negeri 93 Palembang. The technique used in this research was cluster random sampling so that a sample of class VC was obtained as the experimental class and class VB as the control class. There are two data collection techniques in this research, namely a critical thinking ability test and a non-test (questionnaire) on interest in learning and the data analysis technique used is Two-Way ANOVA. Based on the results of the data analysis carried out, the results obtained are: (1) There is an influence of the Contextual Teaching and Learning approach on the critical thinking abilities of students at SD Negeri 93 Palembang (2) There are differences in critical thinking abilities based on students' interest in learning (high, medium, low) SD Negeri 93 Palembang (3) There is no interaction between learning approaches and interest in learning on students' critical thinking skills at SD Negeri 93 Palembang.